Assessing the Role of European Attitudes in Cross-National Research: Does the Post-Communist Context Matter?. (May 2015) - Giurcanu, Magda
How does Eastern Europe contribute to the debate over EU's democratic deficit from an electoral perspective? Does Eastern Europe challenge our theoretical understanding of what motivates European citizens to participate and express their opinions in European Parliamentary elections? While there is no overarching consensus in the academic community regarding these questions, this essay aims to illustrate how a deeper understanding of one post-communist case and a bottom-up perspective on attitudes and political behavior in one locale, Romania, allowed the researcher to delve deeper into the taken-for-granted dynamics that European citizens from the South, East, and West engage in when voting in European Parliamentary elections. The approach of "ethnographic sensibility" mentioned in the workshop's discussions and illustrated in several contributions to this volume (see e.g. Kubik 2013; Knott 2015) constitutes then a useful starting point in deconstructing conventional knowledge. Moreover, during the process of moving up the ladder of generality and building inferences from one case study to a region, Eastern Europe still shares enough characteristics to deserve its own dummy variable, so to speak, in large- N continent-wide analyses covering the 2004 and 2009 European Parliamentary (EP) elections. Yet, as Joshua Tucker (2015) mentions in his contribution, it is unclear whether the historical legacies discussed at the workshop and further elaborated on by Grigore Pop-Eleches (2015) will continue to play a role in a priori distinguishing Eastern Europeans' political attitudes and behaviors from other EU citizens in the South or West in future EP elections.